Tingkat Keterjangkauan Pegawai Negeri Sipil (PNS) Berpenghasilan Rendah terhadap Perumahan Formal di Kota Semarang (Studi Kasus: Pegawai Negeri Sipil Golongan I dan II di Universitas Diponegoro) - Jauhari, Ahmad Rifqi; Manaf, Asnawi (Magister Pembangunan Wilayah dan Kota,Undip, 2014)
Housing is a right for everyone, especially low-income people and civil servants. However, based on The Ministry of Public Housing, 30.8 % of the total numbers of civil servants in Indonesia didâ€™t have a home. They just a ride and rent a house. To overcome these problems, the government has cooperated with stakeholders to provide cheap, subsidized housing and made the subsidy policies to low-income people and Â civil servants. However, based on fact, 16 % of civil servants class I and II, Diponegoro University havenâ€™t own a home and 64 % of them living in informal housing. Why?